2014
DOI: 10.1021/nn5060333
|View full text |Cite
|
Sign up to set email alerts
|

Spectroscopic Fingerprints of Work-Function-Controlled Phthalocyanine Charging on Metal Surfaces

Abstract: The electronic character of a π-conjugated molecular overlayer on a metal surface can change from semiconducting to metallic, depending on how molecular orbitals arrange with respect to the electrode's Fermi level. Molecular level alignment is thus a key property that strongly influences the performance of organic-based devices. In this work, we report how the electronic level alignment of copper phthalocyanines on metal surfaces can be tailored by controlling the substrate work function. We even show the way … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
57
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(65 citation statements)
references
References 49 publications
(128 reference statements)
7
57
1
Order By: Relevance
“…5 These interesting properties of MPcs have spurred significant interest in the adsorption of metal phthalocyanines on single crystal surfaces of materials such as copper, silver, and aluminium. [6][7][8][9] Surface-driven modification of the molecular properties plays an important role, and recent research into phthalocyanine compounds includes the control of the Kondo effect, 10 switching of magnetic anisotropy, 11 and uneven charge transfer leading to distortion and symmetry reduction. 12 The preparation of MPc monolayers (ML) on metal surfaces by thermal evaporation onto the room temperature surface is often tedious since it is difficult to determine the exact amount of deposited material.…”
Section: Introductionmentioning
confidence: 99%
“…5 These interesting properties of MPcs have spurred significant interest in the adsorption of metal phthalocyanines on single crystal surfaces of materials such as copper, silver, and aluminium. [6][7][8][9] Surface-driven modification of the molecular properties plays an important role, and recent research into phthalocyanine compounds includes the control of the Kondo effect, 10 switching of magnetic anisotropy, 11 and uneven charge transfer leading to distortion and symmetry reduction. 12 The preparation of MPc monolayers (ML) on metal surfaces by thermal evaporation onto the room temperature surface is often tedious since it is difficult to determine the exact amount of deposited material.…”
Section: Introductionmentioning
confidence: 99%
“…Borghetti et al . reported that a CuPc layer on Ag(111) is charged negatively, while that on Au(111) remains neutral 38 . Although the charge state of the molecules and their stability strongly depend on the energy alignment and atomic scale details at the junction, three charge states of CuPc, i .…”
Section: Resultsmentioning
confidence: 99%
“…Borghetti et al have argued that the strong electron-accepting nature of this molecule leads to a notable charge transfer from the metal substrates into the F 16 CuPc LUMO, thus counteracting the omnipresent pushback effect. [49] Corresponding STM data show that the adlayer structures for F 16 CuPc on Au(111) (c.f. Figure 1f and Ag(111) (see Supporting Information) are consistent with structures reported in the literature.…”
Section: Non-polar Phthalocyaninesmentioning
confidence: 99%
“…For higher coverage, ΔΦ for Ag(111) (cf. [36,44,48,49] Theoretical investigations show that partial charge transfer depends sensitively on the position of the former LUMO relative to the Fermi level of the substrate, but precise calculation of the coverage dependence remains challenging. For Au(111), on the other hand, a further reduction of 150 meV is observed after completion of the first ML.…”
Section: Non-polar Phthalocyaninesmentioning
confidence: 99%
See 1 more Smart Citation